2010
DOI: 10.2147/imcrj.s9729
|View full text |Cite
|
Sign up to set email alerts
|

Large gastrointestinal stromal tumor size does not imply early recurrence

Abstract: A 28-year-old female presented with a huge intra-abdominal mass. Initially a mesenteric mass was diagnosed, but her tumor was found to be a gastrointestinal stromal tumor (GIST). Laparotomy was performed. The mass was resected en bloc with clear surgical margins in January 2007. It was found to be 20 × 18 × 16 cm. In order to remove the tumor, the left half of transverse colon with its mesocolon, spleen, body and tail of pancreas, and a part of the small intestine had to be removed. The mass was tightly attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…1.802–24.653, p-value 0.004). The correlation between tumor size and mitotic index shows a statistical significance (p-value 0.036) in mitotic count more than 6 HPF by independent to size of tumor which like some report has shown the size not correlated with the risk of recurrence [ 8 ]. Finally, these data were interpreted that only mitotic index more than 6 HPF affected recurrence or metastasis and does not depend on tumor size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.802–24.653, p-value 0.004). The correlation between tumor size and mitotic index shows a statistical significance (p-value 0.036) in mitotic count more than 6 HPF by independent to size of tumor which like some report has shown the size not correlated with the risk of recurrence [ 8 ]. Finally, these data were interpreted that only mitotic index more than 6 HPF affected recurrence or metastasis and does not depend on tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Because GIST are heterogeneous of clinical and morphology which are difficult to predict the prognosis of the disease [ 7 ]. Few studies have focused on the specific risks of solely gastric GIST and some reports have shown the size not correlated the risk of recurrence [ 8 ]. Therefore, the primary aim of this study was to evaluate the risk of recurrence and metastasis of solely gastric GIST receiving curative resection.…”
Section: Introductionmentioning
confidence: 99%
“…Because giant GISTs often invade adjacent organs, tumour rupture and bleeding are likely during surgery. Therefore, complete removal of the tumour may require excision of multiple organs . In the present study, there were some patients with severe anaemia in whom emergency surgery was not indicated.…”
Section: Discussionmentioning
confidence: 73%
“…However, approximately 30% to 50% of GIST patients who underwent complete resection may experience tumor progression within 2 years postoperatively, particularly those with GISTs >10 cm, 4 , 5 thereby affecting long-term outcomes. Combined resection may be adopted for GISTs ≥10 cm because of invasion into adjacent organs, 6 , 7 and the proportion of tumor rupture and extensive intraoperative hemorrhage may also increase at surgery. As a consequence, treating giant GISTs is often a challenge for the attending clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous patients with GISTs ≥10 cm have been described, but most reports present case reports. 6 , 13 – 15 In a retrospective study by Wada et al 7 , they reported the prognoses of this subset of patients, but no patient underwent neoadjuvant or adjuvant treatment until recurrence. Hence, clinical management and prognostic predictors remain unknown.…”
Section: Introductionmentioning
confidence: 99%